2020
DOI: 10.3389/fbioe.2019.00436
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Graphene Enhances Neural Stem Cell Proliferation Through Metabolic Regulation

Abstract: Graphene consists of two-dimensional sp2-bonded carbon sheets, a single or a few layers thick, which has attracted considerable interest in recent years due to its good conductivity and biocompatibility. Three-dimensional graphene foam (3DG) has been demonstrated to be a robust scaffold for culturing neural stem cells (NSCs) in vitro that not only supports NSCs growth, but also maintains cells in a more active proliferative state than 2D graphene films and ordinary glass. In addition, 3DG can enhance NSCs diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 85 publications
1
38
0
Order By: Relevance
“…With the development of biomaterials, topography has become a promising physical cue for manipulating cell behaviors during neural regeneration (Guo et al, 2016;He et al, 2016;Jiang et al, 2016;Severino et al, 2016;Liu et al, 2018;Han et al, 2019;Tang et al, 2019;Xia et al, 2019;Fang et al, 2020). The topography of these materials influences the mechanosensory apparatus and the spatiotemporal dynamics of the cells (Chen et al, 2014), and these cell-material interactions play a key factor in cell behavior regulation (Guilak et al, 2009;Zangi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of biomaterials, topography has become a promising physical cue for manipulating cell behaviors during neural regeneration (Guo et al, 2016;He et al, 2016;Jiang et al, 2016;Severino et al, 2016;Liu et al, 2018;Han et al, 2019;Tang et al, 2019;Xia et al, 2019;Fang et al, 2020). The topography of these materials influences the mechanosensory apparatus and the spatiotemporal dynamics of the cells (Chen et al, 2014), and these cell-material interactions play a key factor in cell behavior regulation (Guilak et al, 2009;Zangi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation generated by CI itself may also be one of the important factors to affect the survival of residual SGNs. Previous studies have reported that the electric conductive biomaterials and the electrical stimulation have very obvious effects on regulating the proliferation and differentiation of neural stem cells [ 44 , 45 ], as well as on regulating the survival and maturation of neurons, including SGNs [ 46 ]. In this study, we found that electrical stimulation could decrease the I Ca but had no effect on the action potential firing in cultured SGNs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study showed that 3D graphene structures enhances NSCs proliferation through glucose metabolism. [ 176 ] Recently, NSCs were seeded as a model on graphene substrates to assess the changes in resting and action membrane potentials in proliferation and differentiation states. [ 177 ] The basic membrane electrical parameters in terms of capacitance and input resistance were not changed; while the resting membrane potentials of cells were significantly negative at both proliferation and differentiation states.…”
Section: Carbon‐based Materialsmentioning
confidence: 99%